Facilitating mental health research for patients, clinicians and researchers: a mixed-method study. Issue 8 (8th August 2016) - Robotham, D; Waterman, S; Oduola, S; Papoulias, C; Craig, T; Wykes, T
Abstract : Objectives: Research registers using Consent for Contact (C4C) can facilitate recruitment into mental health research studies, allowing investigators to contact patients based on clinical records information. We investigated whether such a register was useful for mental health research, seeking the perspectives of patients and research investigators. Setting and design: In 2012, a C4C register was developed in a large secondary mental health provider within the UK; almost 9000 patients have joined. This mixed-method study audited the effectiveness of the register. Participants: A 'mystery shopper' exercise was conducted, and patients (n=21) were recruited to ask clinicians about the availability of research opportunities. Structured interviews were conducted with patients (n=52) about their experiences of being on the register. Similar interviews were conducted with 18 investigators from 19 studies, who had attempted to use the register to recruit participants. Outcome measures: The impact of C4C on study recruitment, and whether it helped patients learn about research. Results: So far, the register has provided 928 individuals with 1085 research opportunities (in 60% of cases, the individual agreed to participate in the study). Clinicians were willing to link patients to research opportunities, but often lacked information about studies. For patients, the register provided opportunities which they may not otherwise have; 27 of 52 had participated in studies since joining the register (18 participating for the first time). Most investigators used the register to supplement recruitment to their studies, but described problems in prescreening potential participants from a clinical record for complex studies. Conclusions: Although the register helped investigators recruit for studies, and provided patients with research opportunities, clinicians' input is still useful for identifying suitable participants. C4C registers should be adapted to provide clinicians with automatically updated information on local studies allowing them to match patients on their caseload with active studies.